Micro-redes de solidariedade e legitimação: A liderança de mulheres na periferia do poder clérigo-institucional das igrejas pentecostais clássicas na cidade de Diadema - Martins, Marcos José (2011)
Women had an active and essential participation since the emergence of Pentecostal Movement for its consolidation. Nevertheless, Pentecostal Movement institutionalization began to segregate women, restricting her operations to subordinate ecclesiastical services. Women were relegated to oblivion. However, the hegemony of male power has not stopped the women to create their own networks of meaning in the Pentecostal churches, by the women's societies that works as territories for socialization and humanization, usually in situations of high social vulnerability. This research aims to visualize and discuss these social and meaning construction networks. The object of this research is micro-social networks composed and led by Pentecostal women. The research method used was the Oral History, which was very useful to understand, by interviews, how they constitute the webs, plots, interactions and networks through flow the solidarity among women and the legitimization of power that own Pentecostal women reach and enjoy in these micro-networks. We tried to let women speak for themselves. With time and the voice, the Pentecostal women!